Α-pyrones and their hydroxylated analogs as promising scaffolds against Mycobacterium tuberculosis. (November 2017) - Bhat, Zubair Shanib; Rather, Muzafar Ahmad; Syed, Khalid Yousuf; Ahmad, Zahoor
Tuberculosis ranks as the leading cause of global human mortality from a single infectious agent. To address the uprising issues of drug resistance, intense research efforts have been directed towards drug discovery. However, it is a long and economically challenging process that is often associated with high failure rates. Therefore, it seems prudent to take forward the core scaffolds that have already acclaimed clinical relevance. In this direction, hydroxylated α-pyrone scaffold has received US FDA approval for human use against HIV. Interestingly, literature review reveals the potential applicability of α-pyrones in TB drug discovery. On one hand, α-pyrones play a vital role in the cell wall of Mycobacterium tuberculosis and on the other hand natural α-pyrones display appreciable anti-TB activity. This review aims to rekindle the interest of researchers toward α-pyrone as a new anti-TB drug that may possibly tackle drug resistance and open a dual frontier in TB and HIV drug discovery.